Venlafaxine besylate monohydrate - Corvalán Moya, Carolina del Huerto (2013)
The title compound {systematic name: [2-(1-hydroxycyclohexyl)-2-(4-methoxyphenyl)ethyl]dimethylazanium benzenesulfonate monohydrate}, C17H28NO2+·C6H5O3S-·H2O, is a besylate salt hydrate of the antidepressant drug venlafaxine. In the crystal, besylate anions and water molecules self-assemble, forming hydrogen-bonded dimers linked around inversion centers, with graph set R44(6). The crystal packing features a chain of alternate dimers and venlafaxine cations in the b-axis direction with the components linked by O-H...O hydrogen bonds and C-H...O and C-H...[pi] interactions. This is the first example of a venlafaxine cation with a closed conformation, as it features an intramolecular N-H...O interaction involving the protonated N atom.